Elimination of biliary stones through the urinary tract: a complication of the laparoscopic cholecystectomy - Castro,Maurício Gustavo Bravim de (1999)
The introduction and popularization of laparoscopic cholecystectomy has been accompanied with a considerable increase in perforation of gallbladder during this procedure (10%--32%), with the occurrence of intraperitoneal bile spillage and the consequent increase in the incidence of lost gallstones (0.2%--20%). Recently the complications associated with these stones have been documented in the literature. We report a rare complication occurring in an 81-year-old woman who underwent laparoscopic cholecystectomy and developed cutaneous fistula to the umbilicus and elimination of biliary stones through the urinary tract. During the cholecystectomy, the gall bladder was perforated, and bile and gallstones were spilled into the peritoneal cavity. Two months after the initial procedure there was exteriorization of fistula through the umbilicus, with intermittent elimination of biliary stones. After eleven months, acute urinary retention occurred due to biliary stones in the bladder, which were removed by cystoscopy. We conclude that efforts should be concentrated on avoiding the spillage of stones during the surgery, and that no rules exist for indicating a laparotomy simply to retrieve these lost gallstones.